2013
DOI: 10.1038/aja.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

Effects of circumcision on male sexual functions: a systematic review and meta-analysis

Abstract: This meta-analysis was performed to assess sexual functions following adult male circumcision. We searched the Cochrane Central Register of Controlled Trials, PUBMED, EMBASE, the Cochrane Database of Systematic Review and Web of Science from their inception until January 2013 to identify all eligible studies that reported on men's sexual function after circumcision. The Cochrane Collaboration's RevMan 5.2 software was employed for data analysis, and the fixed or the random effect model was selected depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 36 publications
1
74
0
2
Order By: Relevance
“…Systematic reviews have found no adverse effect of MC on sexual function, 28 , 29 , 33 sensitivity, or satisfaction 29 . A meta-analysis of all common male sexual dysfunctions found none were related to MC status 28 . Furthermore, the third British National Survey of Sexual Attitudes and Lifestyles (Natsal-3), a large national probability survey, which used a new, comprehensive, validated measure of sexual function, the Natsal-SF, presented findings for 6,293 men and 8,869 women aged 16–74 years, broadly representative of the British population.…”
Section: Benefits Versus Risksmentioning
confidence: 99%
“…Systematic reviews have found no adverse effect of MC on sexual function, 28 , 29 , 33 sensitivity, or satisfaction 29 . A meta-analysis of all common male sexual dysfunctions found none were related to MC status 28 . Furthermore, the third British National Survey of Sexual Attitudes and Lifestyles (Natsal-3), a large national probability survey, which used a new, comprehensive, validated measure of sexual function, the Natsal-SF, presented findings for 6,293 men and 8,869 women aged 16–74 years, broadly representative of the British population.…”
Section: Benefits Versus Risksmentioning
confidence: 99%
“…A recent meta-analysis included 10 studies to assess the impact of MC on sexual function 72 . There were no significant differences in sexual desire, dyspareunia, premature ejaculation, ejaculation latency time or erectile dysfunctions between circumcised and uncircumcised men.…”
Section: Role Of the Foreskin In Sensation And Sexual Functionmentioning
confidence: 99%
“…There is scant evidence to suggest that men's perceptions of improved sexual performance post-circumcision (e.g., more potent erections, increased sexual desire, and increased time to ejaculation) is caused by the removal of the man's foreskin. A systematic review of rigorous clinical studies and a separate meta-analysis indicated no significant differences in time to ejaculation, premature ejaculation, or sexual desire between circumcised men and uncircumcised men (Morris & Krieger, 2013; Tian et al, 2013). There is significant social meaning attached to the penis and its performance during sex (Castro-Vázquez, 2013a; Reeser, 2010; Richters, 2006) and thus men's sexual performance following VMMC is more complex than the simple removal of one's foreskin.…”
Section: Discussionmentioning
confidence: 99%